A Comparison of Problem-Based Learning and Inquiry Learning Models Using a Deep Learning Approach on the Topic of Environmental Change and Its Impact on Critical Thinking Skills - Latifah Windasari; Ervan Johan Wicaksana; Fitri Astriawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Critical thinking is the process of thinking clearly and logically when evaluating information. It involves using cognitive abilities to identify, analyse and evaluate information in order to solve problems and draw the right conclusions. This study aims to analyse the impact of implementing Problem-Based Learning (PBL) and Inquiry Learning models alongside a deep learning approach on critical thinking skills in environmental studies. The research used a quasi-experimental design with a non-randomised control group pretest-posttest. The study's participants were 61 pupils selected through purposive sampling. Critical thinking skills were measured using an essay test based on the following six Ennis indicators: Focus, Reason, Inference, Situation, Clarity, and Overview. The data were analysed using One Way ANOVA. The results showed no significant difference in critical thinking skills (F(1, 29) = 0.022, p = 0.883, ηp² = 0.001). Therefore, it can be concluded that implementing the PBL and Inquiry Learning models with a deep learning approach has the same impact on students' critical thinking skills.Critical thinking is the process of thinking clearly and logically when evaluating information. It involves using cognitive abilities to identify, analyse and evaluate information in order to solve problems and draw the right conclusions. This study aims to analyse the impact of implementing Problem-Based Learning (PBL) and Inquiry Learning models alongside a deep learning approach on critical thinking skills in environmental studies. The research used a quasi-experimental design with a non-randomised control group pretest-posttest. The study's participants were 61 pupils selected through purposive sampling. Critical thinking skills were measured using an essay test based on the following six Ennis indicators: Focus, Reason, Inference, Situation, Clarity, and Overview. The data were analysed using One Way ANOVA. The results showed no significant difference in critical thinking skills (F(1, 29) = 0.022, p = 0.883, η_p² = 0.001). Therefore, it can be concluded that implementing the PBL and Inquiry Learning models with a deep learning approach has the same impact on students' critical thinking skills.